VD_FINDINFO Jug / 2022 / 127 vom 10. Februar 2022 - VD Tribunal cantonal (2022)
FIXATION DE LA PEINE, PEINE D'ENSEMBLE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, CONCOURS D'INFRACTIONS | 43 al. 1 CP, 47 CP, 49 al. 1 CP